2013
DOI: 10.1016/j.jalz.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor polymorphisms and incident dementia: The prospective 3C study

Abstract: BackgroundGenetic variation in the estrogen receptor (ESR) may be associated with the incidence of Alzheimer's disease (AD), but this association could be modified by genetic and environmental factors.MethodsThe association between five ESR α (ESR1) and β (ESR2) polymorphisms with 7‐year dementia incidence was examined among 6959 older men and women from the Three City Study using multivariate‐adjusted Cox regression models with delayed entry. Gender, the apolipoprotein E (APOE) ε4 allele, and hormone treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…However, significant associations with the ERβ polymorphism, rs1256049, were identified including an increased risk of substantial decline in visual memory, psychomotor speed, and on the incidence of MCI (Ryan et al, 2013). Further analysis indicated that, in support of the initial finding of a significant interaction between ERα and ERβ polymorphisms and the risk for AD (Lambert et al, 2001), the association between ERβ polymorphism and AD appeared to be modified by ERα polymorphism (Ryan et al, 2014). Interestingly, the same study showed a slight association between the minor allele of the ERβ SNP, rs4986938, and a decreased risk of decline in psychomotor speed (Ryan et al, 2013).…”
Section: Erβ Polymorphisms In Admentioning
confidence: 75%
“…However, significant associations with the ERβ polymorphism, rs1256049, were identified including an increased risk of substantial decline in visual memory, psychomotor speed, and on the incidence of MCI (Ryan et al, 2013). Further analysis indicated that, in support of the initial finding of a significant interaction between ERα and ERβ polymorphisms and the risk for AD (Lambert et al, 2001), the association between ERβ polymorphism and AD appeared to be modified by ERα polymorphism (Ryan et al, 2014). Interestingly, the same study showed a slight association between the minor allele of the ERβ SNP, rs4986938, and a decreased risk of decline in psychomotor speed (Ryan et al, 2013).…”
Section: Erβ Polymorphisms In Admentioning
confidence: 75%
“…Estrogen receptors play a key and contrasting role in regulation of ApoE gene and protein expression (33) and risk of AD(141). ERα up-regulated ApoE mRNA and protein expression whereas in contrast, ERβ down-regulated ApoE mRNA and protein expression(33).…”
Section: Sex Differences In Apoe Genotype and Risk Of Alzheimer’smentioning
confidence: 99%
“…These data suggest that use of ER-selective ligands could provide therapeutic benefit to reduce the risk of AD by increasing ApoE expression in ApoE 2 or 3 allele carriers and decreasing ApoE expression in ApoE4 allele carriers. Polymorphisms in both estrogen receptor alpha (rs4986938) and estrogen receptor β (rs2234693) have been associated with increased risk of dementia and AD (141). …”
Section: Sex Differences In Apoe Genotype and Risk Of Alzheimer’smentioning
confidence: 99%
“…A recent study proposed that one dominant negative splice variant, ERβ2, may mediate differential responses to E 2 treatment early and late after ovariectomy (OVX) in rats, such that only if estrogen treatment is initiated early after OVX is it able to prevent induction of the dominant negative ERβ2 variant (Wang et al, 2012). In addition to splice variants, there are several ERα polymorphisms that increase the risk of Alzheimer’s disease (AD) specifically in women, particularly when associated with the APOE ε4 allele (Ryan et al, 2013). …”
Section: Estrogen Estrogen Receptors and Intracellular Signalingmentioning
confidence: 99%